Cleanliness of equipment in pharmaceutical enterprises (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This thesis about Cleanliness of equipment in pharmaceutical enterprises. Cleaning pharmaceutical processing equipment is challenging. Cleaning methods, soils present, type of manufacturing equipment, surfaces cleaned, choice of cleaning detergent and temperature should all be considered when setting up a cleaning procedure. Cleaning validation methods are required. The entire cleaning process must be standardized and documented according to the FDA’s cGMP regulations.